Angiosarcoma of the Gallbladder: Case Report and Review of the Literature - Alexandre N Odashiro; Patricia Rusa Pereira; Luciana N Odashiro Miiji; Gia-Khanh Nguyen (Canadian Journal of Gastroenterology)
A 62-year-old white woman with an unremarkable past medical history presented with acute cholecystitis. A cholecystectomy was performed, revealing an acute hemorrhagic and chronic cholecystitis associated with cholelithiasis. Two months after the operation, the patient developed a massive hemoperitoneum and died by hypo-volemic shock. At autopsy, an angiosarcoma measuring 5 cm in diameter was found in the liver, at the site of the gallbladder fossa. There were multiple hepatic, splenic, ovarian and peritoneal metastases and a massive hemoperitoneum consisting of 8 L of blood and blood clots. Review of the tissue sections from the patient's gallbladder confirmed the presence of an acute hemorrhagic and chronic cholecystitis and also revealed residual foci of an angiosarcoma. A review of eight previously reported cases of gallbladder angiosarcoma is also presented.